Lectura i cultura de la dona a l'edat mitjana: opinions d'autors en català - Cantavella, Rosanna (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: The access of women to literature was the object of diatribes of many Catalonian medieval writers, but in the 15th century it became a socially accepted fact.